Étude des modes d’approvisionnement en eau potable et des stratégies de réhabilitation des points d’eau modernes ruraux en zone tropicale humide : cas de la Commune de Mvangan au Cameroun - Victor Dang Mvongo; Théophile Fonkou; Célestin Defo (VertigO)
This article aims to provide local information on access to drinking water and service management models in the Mvangan Council (Southern-Cameroon). Specifically, the article provides an overview of access to safe drinking water in Mvangan Council, makes a critical analysis of the management model put in place and proposes solutions to improve water service. The data were collected from field visit, direct observations, interviews of water users and questionnaire administered to the water point management committee. The results revealed that in the Mvangan Council there are one hundred and twenty-seven (127) modern water points including eighty-four (84) wells, eleven (11) boreholes and thirty-two (32) springs. It was observed that about 62% of the water points were fully in service, 75% hand pumps were found in good conditions, and that yielded 74.34% of water point needs were covered. The maintenance of the water points was carried out by the Mvangan municipal management. The irregularity of monitoring, the weak functionality of the Committees of Water Points Management (CWPMs), the weak structuring of the maintenance chain, the low financial flows generated by the water commercialization, and the lack of culture of water sale in the community were the main constraints that affect the sustainability of water services in Mvangan Council. These inadequacies are the result of the incomplete implementation of the ongoing decentralization process in Cameroon and most countries in West and Central Africa. Also, the completion of the maintenance of the works under management and more generally the pooling of water services at the level of several municipalities is a promising avenue of action to improve the sustainability of services in Cameroon and West and Central Africa.